1988
DOI: 10.1177/174114328801600106
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Implementation of Grids in one Local Education Authority

Abstract: The introduction of GRIDS for schools to review their curricula was received positively. Teachers welcomed their greater involvement in decisions and better communications. Further work was found to be needed on the processes of change in schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The case study of Green Lane (Webb, 1996) also demonstrates the power of collaborative cultures to sustain staff through exceedingly difficult circumstances and to enable them to work together to bring about externally imposed change. In an evaluation of the implementation of GRIDS in one LEA, Constable et al (1988) found that for GRIDS to be operated successfully, teachers needed to be accustomed to working cooperatively and had to have a genuine concern for the school as a whole, which took precedence over more parochial concerns, and an appreciation of the need for change. The demands of the Education Reform Act (1988) and subsequent legislation have fostered such qualities and attitudes, suggesting that now school-based evaluation could prove much more effective in England than in the 1980s.…”
Section: Resultsmentioning
confidence: 99%
“…The case study of Green Lane (Webb, 1996) also demonstrates the power of collaborative cultures to sustain staff through exceedingly difficult circumstances and to enable them to work together to bring about externally imposed change. In an evaluation of the implementation of GRIDS in one LEA, Constable et al (1988) found that for GRIDS to be operated successfully, teachers needed to be accustomed to working cooperatively and had to have a genuine concern for the school as a whole, which took precedence over more parochial concerns, and an appreciation of the need for change. The demands of the Education Reform Act (1988) and subsequent legislation have fostered such qualities and attitudes, suggesting that now school-based evaluation could prove much more effective in England than in the 1980s.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of the Exploratory Group was therefore to illuminate and complement these, rather than act as a precursor to the entire study. The study itself was an evaluation of the implementation of GRIDS in Leeds schools (see Constable et al, 1988). The Guidelines for Review and Internal Development in Schools (McMahon et al, 1984) is a process for conducting school self-review.…”
Section: Examples Of Exploratory Groupsmentioning
confidence: 99%